If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4x + -2) + 8x = 5x + -6 Reorder the terms: -5(-2 + 4x) + 8x = 5x + -6 (-2 * -5 + 4x * -5) + 8x = 5x + -6 (10 + -20x) + 8x = 5x + -6 Combine like terms: -20x + 8x = -12x 10 + -12x = 5x + -6 Reorder the terms: 10 + -12x = -6 + 5x Solving 10 + -12x = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10 + -12x + -5x = -6 + 5x + -5x Combine like terms: -12x + -5x = -17x 10 + -17x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 10 + -17x = -6 + 0 10 + -17x = -6 Add '-10' to each side of the equation. 10 + -10 + -17x = -6 + -10 Combine like terms: 10 + -10 = 0 0 + -17x = -6 + -10 -17x = -6 + -10 Combine like terms: -6 + -10 = -16 -17x = -16 Divide each side by '-17'. x = 0.9411764706 Simplifying x = 0.9411764706
| 2m-15p-3mp+10= | | 6x-12+15x+30= | | -6+2(x+5)=8(x-8)-10x | | 2(3x+5)=1x+8+5x | | 2(3x+5)=1x+8x+5x | | 7-1.2x=3 | | X*x*x-4x*4x=0 | | 4-(n-4)=3(3+2) | | 64x^3-125y^3= | | -5(k-3)+5=6k-5(k+2) | | 2n-3-7=n-2-5 | | 2.3m=1.2 | | 32x-16y=96 | | t^2-5t=24 | | 2x-5=x-1-3 | | -5v+-8v=13 | | 2(8-3y)=4y-9 | | 5(-6x-1)=5(3-7x) | | 18n^2-8= | | 3-5=x+2-6 | | 60=k-3 | | 128x^3-250y^3= | | x+2-5=7-5 | | -37-8n=6n+7(1+6n) | | -5(a-3)-3=-6a+7(a+1) | | x^3=2y^2 | | 7.1x+1=6.1x | | (3a-5)(4a+7)= | | -18+m=7m+6(4m+2) | | -(7+7k)+8(-6k+8)=2 | | 0.5x+0.2=0.9x-2.2 | | 6(x+3)-9=2x+4(1+x) |